A Discourse Analysis Of National Scene Column On The Jakarta Post - Widyastuti, Nurfita, Dra. Malikatul Laila, M. Hum, Dra. Siti Zuhriah Ariatmi, M. Hum (2015)
This research is aimed in identifying and describing the non-linguistic context of the discourse on National Scene Column in The Jakarta Post. The research conducted by the writer is descriptive qualitative research. The data of this research are some short discourse that chosen from newspaper, while the data source is taken from Jakarta Post published in May 2015. The method used by the writer in collecting data is documentation with step: reading, selecting, classifying, signing, and coding the data. In analyzing the data, the writer describes the elements of the news by David Nunan and explaining the elements of the news by elaborating the news. The result of the study shows that all types of discourse of the National Scene Column are news discourse. There are two kinds of the writer's intentions in writing the discourse of National Scene Column; informative and persuasive.